Syria: double “battlefront” during COVID-19 era - Karaleka, Antonia-Nefeli (HAPSc Policy Briefs Series, 2020)
For many countries, the COVID-19 health crisis has been the biggest challenge of the last decades. However, for Syria it has been included to an already long list of challenges. How did Syria managed the first wave of the pandemic and what were the results? Is the country now more experienced and ready to face a possible second wave of COVID-19? How could Syria have worked more effectively during the last three months and how will it take advantage of this experience to get equipped for the near future. And most importantly, what is the involvement and which are the results of foreign authorities and countries’ involvement? This study will attempt to answer these questions about Syria, a country that has been at the forefront of political developments for the past nine years.